The Role of Scouting Extracurricular Activities in Developing Emotional Intelligence and Discipline in Junior High School Students - Muhamad Alfiyan Ariyanto; Ellen Prima (Journal of Contemporary Pedagogy and Learning Science, 2026)
Scouting extracurricular activities are widely recognized as an important medium for character education and socio-emotional development among students. This study aims to examine the role of scouting extracurricular activities in developing emotional intelligence and disciplinary character among junior high school students. The study employed a qualitative non-empirical approach using a literature review design. Data were collected from scholarly journals, books, and relevant academic publications addressing scouting education, emotional intelligence, discipline, and student development. The findings indicate that scouting activities contribute to the development of self-awareness, emotional regulation, empathy, responsibility, and social competence through experiential and collaborative learning experiences. The review also reveals a strong relationship between emotional intelligence and disciplinary behavior, as students with better emotional regulation tend to demonstrate greater self-control, accountability, and adherence to rules. In addition, scouting activities promote broader developmental outcomes, including leadership, independence, social responsibility, and civic awareness. These findings highlight the significance of scouting as a character-based learning environment that supports holistic student development and strengthens both socio-emotional competencies and disciplinary character.